Pro-inflammatory role of Wnt/β-catenin signaling in endothelial dysfunction - Wadey, Kerry S.; Somos, Alexandros; Leyden, Genevieve; Blythe, Hazel; Chan, Jeremy; Hutchinson, Lawrence; Poole, Alastair; Frankow, Aleksandra; Johnson, Jason L.; George, Sarah J. (Frontiers in Cardiovascular Medicine, 2023)
Background Endothelial dysfunction is a critical component of both atherosclerotic plaque formation and saphenous vein graft failure. Crosstalk between the pro-inflammatory TNF-α-NFκB signaling axis and the canonical Wnt/β-catenin signaling pathway potentially plays an important role in regulating endothelial dysfunction, though the exact nature of this is not defined. Results In this study, cultured endothelial cells were challenged with TNF-α and the potential of a Wnt/β-catenin signaling inhibitor, iCRT-14, in reversing the adverse effects of TNF-α on endothelial physiology was evaluated. Treatment with iCRT-14 lowered nuclear and total NFκB protein levels, as well as expression of NFκB target genes, IL-8 and MCP-1. Inhibition of β-catenin activity with iCRT-14 suppressed TNF-α-induced monocyte adhesion and decreased VCAM-1 protein levels. Treatment with iCRT-14 also restored endothelial barrier function and increased levels of ZO-1 and focal adhesion-associated phospho-paxillin (Tyr118). Interestingly, inhibition of β-catenin with iCRT-14 enhanced platelet adhesion in cultured TNF-α-stimulated endothelial cells and in an ex vivo human saphenous vein model, most likely via elevating levels of membrane-tethered vWF. Wound healing was moderately retarded by iCRT-14; hence, inhibition of Wnt/β-catenin signaling may interfere with re-endothelialisation in grafted saphenous vein conduits. Conclusion Inhibition of the Wnt/β-catenin signaling pathway with iCRT-14 significantly recovered normal endothelial function by decreasing inflammatory cytokine production, monocyte adhesion and endothelial permeability. However, treatment of cultured endothelial cells with iCRT-14 also exerted a pro-coagulatory and moderate anti-wound healing effect: these factors may affect the suitability of Wnt/β-catenin inhibition as a therapy for atherosclerosis and vein graft failure.